Maybe holier, but definitely less evil, than you Bounded self-righteousness in social judgment. [article]. - Klein, Nadav
Few biases in human judgment are easier to demonstrate than self-righteousness: the tendency to believe one is more moral than others. Existing research, however, has overlooked an important ambiguity in evaluations of one's own and others' moral behavior that could lead to an overly simplistic characterization of self-righteousness. In particular, moral behavior spans a broad spectrum ranging from doing good to doing bad. Self-righteousness could indicate believing that one is more likely to do good than others, less likely to do bad, or both. Based on cognitive and motivational mechanisms, we predicted an asymmetry in the degree of self-righteousness such that it would be larger when considering unethical actions (doing bad) than when considering ethical actions (doing good). A series of experiments confirmed this prediction. A final experiment suggests that this asymmetry is partly produced by the difference in perspectives that people adopt when evaluating themselves and others (Experiment 8). These results all suggest a bounded sense of self-righteousness. Believing one "less evil than thou" seems more reliable than believing one is "holier than thou." -- (from the authors)
Keywords: Epley, Nicholas; Self-evaluation.; Self-esteem.; Self-righteousness.; Social cognition; Moral psychology